Travel as a barrier to abortion provided by law access. Brazil, 2010-2019 - Marina Gasino Jacobs; Alexandra Crispim Boing (Revista Brasileira de Saúde Materno Infantil, 2023)
Abstract Objectives: to analyze abortions provided by law (APL) carried out in Brazil between 2010 and 2019 regarding the need for travel of users, as well as the expenditure of time and money on these trips. Methods: descriptive study of records of outpatient care and hospitalizations for APL between 2010 and 2019. The municipal provision and the inter-municipal flows for the realization of the APL, the availability of public transportation for this travel, as well as its cost and time, were identified. Results: 2.6% of Brazilian municipalities had a sustained provision of APL between 2010 and 2019. Of the 15,889 APL performed, 14.8% occurred in municipalities other than those where the user lived. The smaller the population size of the municipality of residence, the higher the percentage of the need for travel. Of these inter-municipal trips, 16.0% had regular round-trip links by public transport. The total travel time ranged from 26 minutes to 4 and a half days, and the cost from R$2.70 to R$1,218.06; the highest medians were among residents of the Midwest region. Conclusions: the concentration of services, the deficiency of inter-municipal public transport, and the expenditure on travel to access the APL are barriers to users that need the health service, demanding public policies to overcome them.